Doppler ultrasound and fetal activity. - David, H (1975)
The possibility that Doppler ultrasound, as used in routine fetal monitoring by external cardiotocography, might stimulate fetal activity was investigated. A mean increase in fetal activity of over 90% was found, as judged by the fetal movement count.